Muscular involvement in the Holt-Oram syndrome. Issue 12 (December 1997) - Spranger, S; Ulmer, H; Tröger, J; Jansen, O; Graf, J; Meinck, H M; Spranger, M
Abstract : Holt-Oram syndrome is an autosomal dominant disorder characterised by radial ray and congenital heart defects. Recently, a gene for this disorder has been identified on chromosome 12q24.1, encoding a T box transcription factor. However, the functional role of the gene product is not completely understood. We present results of neurological, radiological, and muscle magnetic resonance imaging (MRI) investigations in 13 patients from eight unrelated families. Besides heart defects, clinical signs ranged from thenar abnormalities to bilateral phocomelia. The former were present in all patients. MRI showed hypoplasia of discrete muscles which clinically showed as non-progressive weakness. The structural pattern of residual muscles was normal on MRI, which together with normal muscular power, electromyography, and muscle enzyme investigations excluded a progressive neuromuscular disorder. The number and location of hypoplastic muscles correlated with the severity of skeletal involvement. Thus, patients with hypoplasia of large and proximal muscles had phocomelia, and those with mere intrinsic hand muscle hypoplasia had only a triphalangeal thumb or no skeletal malformation. On the basis of these observations, we conclude that disturbed fetal limb muscle development is involved in the bony malformations of the upper limbs.